Extrapolating cetacean densities beyond surveyed regions: habitat‐based predictions in the circumtropical belt. (9th May 2015) - Mannocci, Laura; Monestiez, Pascal; Spitz, Jérôme; Ridoux, Vincent
Abstract Aim Our knowledge of cetacean distributions is impeded by large data‐gaps worldwide, particularly at tropical latitudes. This study aims to (1) find generic relationships between cetaceans and their habitats in a range of tropical waters, and (2) extrapolate cetacean densities in a circumtropical belt extending far beyond surveyed regions. Location Pelagic, circumtropical. Methods Aerial surveys were conducted over three regions in the tropical Atlantic (132, 000 km2), Indian (1.4 million km2) and Pacific (1.4 million km2) oceans. Three cetacean guilds were studied (Delphininae, Globicephalinae and sperm and beaked whales). For each guild, a generalized additive model was fitted using sightings recorded in all three regions and 14 candidate environmental predictors. Cetacean densities were tentatively extrapolated over a circumtropical belt, excluding waters where environmental characteristics departed from those encountered in the surveyed regions. Results Each cetacean guild exhibited a relationship with the primary production and depth of the minimum dissolved oxygen concentration. Delphininae also showed a relationship with the dominant phytoplankton group. The prediction envelopes were primarily constrained by water temperature. Circumtropical extrapolations of Delphininae and Globicephalinae were contrasted between ocean basins, with high densities predicted in the equatorial waters of the three ocean basins. The predicted densities of sperm and beaked whales were lower and more uniform across the circumtropical belt than for the other two guilds. Main conclusions Our modelling approach represents a good analytical solution to predicting cetacean population densities in poorly documented tropical waters. Future data collection should concentrate on areas where environmental characteristics were not encountered in our survey regions and where the predicted densities were the most uncertain. By highlighting cetacean hotspots far beyond waters under national jurisdiction, this study can provide guidance for the delimitation of Ecologically and Biologically Significant Marine Areas.